2016
DOI: 10.3390/molecules21050642
|View full text |Cite
|
Sign up to set email alerts
|

A New Canthinone-Type Alkaloid Isolated from Ailanthus altissima Swingle

Abstract: Abstract:The present investigation of the chemical constituents of the stem barks of Ailanthus altissima has resulted in the isolation of six canthinone-type alkaloids, including a new compound, (R)-5-(1-hydroxyethyl)-canthine-6-one (1), and five known compounds (2-6). Moreover, four phenyl propanoids (7-10), two lignans (11 and 12), two triterpenoids (13 and 14) and a fatty acid (15) having previously known chemical structures were isolated during the same course of this study. The structure of the new compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…10-Hydroxy-antirhine N- 11-Hydroxycanthin-6-one-N-oxide Simaroubaceae: Simarouba berteroana Krug & Urban [25] 9-Hydroxycanthin-6-one-N-oxide Simaroubaceae: S. berteroana [25] (R)-5-(1-Hydroxyethyl)canthine-6-one Simaroubaceae: Ailanthus altissima Swingle [18] 10-hydroxy-iso-deppeaninol Rubiaceae: Psychotria prunifolia (Kunth) Steyerm. [29] 1-Hydroxy-11methoxycanthin-6-one Simaroubaceae: Eurycoma longifolia Jack [24] 10-Hydroxy-9methoxycanthin-6-one Simaroubaceae: E. longifolia [21,24] 11-Hydroxy-1methoxycanthin-6-one Simaroubaceae: E. longifolia [21] 11-Hydroxy-10methoxycanthin-6-one Simaroubaceae: E. longifolia [24] 5-Hydroxy-…”
Section: -39]mentioning
confidence: 99%
“…10-Hydroxy-antirhine N- 11-Hydroxycanthin-6-one-N-oxide Simaroubaceae: Simarouba berteroana Krug & Urban [25] 9-Hydroxycanthin-6-one-N-oxide Simaroubaceae: S. berteroana [25] (R)-5-(1-Hydroxyethyl)canthine-6-one Simaroubaceae: Ailanthus altissima Swingle [18] 10-hydroxy-iso-deppeaninol Rubiaceae: Psychotria prunifolia (Kunth) Steyerm. [29] 1-Hydroxy-11methoxycanthin-6-one Simaroubaceae: Eurycoma longifolia Jack [24] 10-Hydroxy-9methoxycanthin-6-one Simaroubaceae: E. longifolia [21,24] 11-Hydroxy-1methoxycanthin-6-one Simaroubaceae: E. longifolia [21] 11-Hydroxy-10methoxycanthin-6-one Simaroubaceae: E. longifolia [24] 5-Hydroxy-…”
Section: -39]mentioning
confidence: 99%
“…Sinapaldehyde (SNAH) is a methoxyphenol found in several plants such as Senra incan [ 21 ], Ailanthus altissima Swingle [ 22 ], Eucalyptus globulus [ 23 ], Oryza sativa [ 24 ], Dendropanax dentiger [ 25 ], and Populus tomentosa [ 26 ]. It was reported that SNAH exerts antibacterial activities against oral pathogenic bacteria, including Streptococcus pyogenes , Streptococcus mitis , and Streptococcus mutans [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tissues of various Ailanthus species contain a large number of biologically active compounds, such as alkaloids, terpenoids, steroids, flavonoids, and volatile oils—about 200 in total [37]. Studies periodically discover new ones, for example, in the A. altissima bark [161] or fruits [162]. Among them, the quassinoids stand out and represent highly oxygenated degraded triterpenes with a bitter taste, which can be found only in the Simaroubaceae family.…”
Section: Allelochemicals In Treesmentioning
confidence: 99%